PENGABDIAN KEPADA MASYARAKAT DALAM PENERAPAN TEKNOLOGI SEBAGAI STRATEGIS PEMASARAN DAN LOGO PADA UMKM AGAR MENINGKATKAN PENJUALAN DI DESA TANJUNG SIRAM - Irmayanti, Junita Lubis, Tetty Rahmiati Harahap, Erni Wahyuni, Rahmi Nazliah, Rizki Amansyah (PT.JNDI, JURNAL BIMA, 2023)
This service aims to apply technology as a marketing strategy and logo for MSMEs to increase sales in Tanjung Siram village. This method of community service is to discuss, socialize and present how to market a product using technology and making a distinctive logo of the product. The results of this activity are expected by the people of Tanjung Siram village to have an increase in sales of MSME products. In community service in this activity for Micro, Small and Medium Enterprises (MSMEs) engaged in the business of food products in Tanjung Siram Village. For MSMEs, it is necessary to provide training in the importance of utilizing Digital marketing Technology so that the marketing system becomes better so as to expand the scope of their business targets. And can support even better sales. MSMEs are also given directions to provide a logo or characteristic of the products they sell to attract the attention of buyers when marketed. These MSMEs are given directions to use technology in the form of social media accounts, instagram, facebook, and how to manage digital media optimally. Applied to Micro and medium enterprises (MSMEs) to use technology that is growing rapidly day by day in this era of increasingly sophisticated technology, where the marketing process that uses digital technology can increase sales more rapidly.